Exploring the chemical space of pharmaceutical extractables and leachables - Lidiya Stavitskaya; Arianna Bassan; R. Daniel Mellon; Patricia Parris; Sadegh Faramarzi; Richard Hutchinson; Candice Johnson; Lance R. Molnar; Deborah Palazzotti; Manuela Pavan; Kevin P. Cross (Regulatory Toxicology and Pharmacology, 2026)

Air pollution exposure assessment for preschool children: Addressing spatial and temporal variations and social inequities - Å.K. Watne; M. Azzouz; P. Molnar; L. Stockfelt; J. Lindén; E. Johansson; M. Laurelin; T. Wisell; H. Lundström; A. Roth; S. Jutterström; J. Moldanova; et al. (Journal of Environmental Management, 2025)

A review of the microtremor horizontal-to-vertical spectral ratio (MHVSR) method - S. Molnar; A. Sirohey; J. Assaf; P.-Y. Bard; S. Castellaro; C. Cornou; B. Cox; B. Guillier; B. Hassani; H. Kawase; S. Matsushima; F. J. Sánchez-Sesma; et al. (Journal of Seismology, 2022)
The single-station microtremor horizontal-to-vertical spectral ratio (MHVSR) method was initially proposed to retrieve the site amplification function and its resonance frequencies produced by unconsolidated sediments overlying high-velocity bedrock. Presently, MHVSR measurements are predominantly conducted to obtain an estimate of the fundamental site frequency at sites where a strong subsurface impedance contrast exists. Of the earthquake site characterization methods presented in this special issue, the MHVSR method is the furthest behind in terms of consensus towards standardized guidelines and commercial use. The greatest challenges to an international standardization of MHVSR acquisition and analysis are (1) the what — the underlying composition of the microtremor wavefield is site-dependent, and thus, the appropriate theoretical (forward) model for inversion is still debated; and (2) the how — many factors and options are involved in the data acquisition, processing, and interpretation stages. This paper reviews briefly a historical development of the MHVSR technique and the physical basis of an MHVSR (the what ). We then summarize recommendations for MHVSR acquisition and analysis (the how ). Specific sections address MHVSR interpretation and uncertainty assessment.

Binge drinking is associated with altered resting state functional connectivity of reward-salience and top down control networks - Donatello Arienzo; Joseph P. Happer; Sean M. Molnar; Austin Alderson-Myers; Ksenija Marinkovic (Brain Imaging and Behavior, 2020)

Comparative mapping of the oat Dw6/dw6 dwarfing locus using NILs and association with vacuolar proton ATPase subunit H - Stephen J. Molnar; Julie T. Chapados; Sivakala Satheeskumar; Charlene P. Wight; Bonnie Bancroft; Winson Orr; Doris E. Luckert; Solomon Kibite (Theoretical and Applied Genetics, 2012)

Norfluoxetine Induces Spawning and Parturition in Estuarine and Freshwater Bivalves - P. P. Fong; N. Molnar (Bulletin of Environmental Contamination and Toxicology, 2008)

Mapping resistance to Southern rust in a tropical by temperate maize recombinant inbred topcross population - M. P. Jines; P. Balint-Kurti; L. A. Robertson-Hoyt; T. Molnar; J. B. Holland; M. M. Goodman (Theoretical and Applied Genetics, 2007)

Identification of molecular markers for aluminium tolerance in diploid oat through comparative mapping and QTL analysis - C. P. Wight; S. Kibite; N. A. Tinker; S. J. Molnar (Theoretical and Applied Genetics, 2006)

A molecular linkage map with associated QTLs from a hulless × covered spring oat population - D. L. De Koeyer; N. A. Tinker; C. P. Wight; J. Deyl; V. D. Burrows; L. S. O’Donoughue; A. Lybaert; S. J. Molnar; K. C. Armstrong; G. Fedak; D. M. Wesenberg; B. G. Rossnagel; et al. (Theoretical and Applied Genetics, 2004)